Answer:
=90[tex]x^{2}[/tex]+2x+3
Step-by-step explanation:
Let's simplify step-by-step.
2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 8 − ( −6[tex]x^{2}[/tex] − 2x + 5 )
Distribute the Negative Sign:
= 2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 8 + − 1 ( − 6[tex]x^{2}[/tex] − 2x + 5 )
= 2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 8 + − 1( − 6[tex]x^{2}[/tex] ) + − 1 ( −2x ) + ( − 1 ) ( 5 )
= 2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 8 + 6[tex]x^{2}[/tex] + 2x + − 5
Combine Like Terms:
= 2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 8 + 6[tex]x^{2}[/tex] + 2x + −5
= ( 2[tex]x^{2}[/tex] + 82[tex]x^{2}[/tex] + 6[tex]x^{2}[/tex] ) + ( 2x ) + ( 8 + − 5 )
= 90[tex]x^{2}[/tex] + 2x + 3
Hope it helps
Please mark me as the brainliest
Thank you